Design of Factorial Experiments in Small Blocks - Jayawardena, Shyamalie (Faculty of Science, University of Colombo, 1987)
The problem this study attempts to answer may be briefly described as follows. How can a factorial experiment be designed in a simple manner making use of whatever available blocks (which may or may not allow equal replication of treatments) so as to be able to estimate the important contrasts with a pre-specified order of precision? ...